2005
DOI: 10.1016/j.neuroimage.2005.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Some neurophysiological constraints on models of word naming

Abstract: The pronunciation of irregular words in deep orthographies like English cannot be specified by simple rules. On the other hand, the fact that novel letter strings can be pronounced seems to imply the existence of such rules. These facts motivate dual-route models of word naming, which postulate separate lexical (whole-word) and non-lexical (rulebased) mechanisms for accessing phonology. We used fMRI during oral naming of irregular words, regular words, and nonwords, to test this theory against a competing sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
233
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(280 citation statements)
references
References 100 publications
42
233
2
3
Order By: Relevance
“…The three regions that showed lexical (word > pseudoword) responses only in the Attend condition are among those frequently identified in imaging studies of semantic processing (e.g., Binder et al, 1999;Binder et al, 2003;Binder et al, 2005;Demonet et al, 1992;Mummery et al, 1998;Price et al, 1997;Roskies et al, 2001;Scott et al, 2003;Spitsyna et al, 2006). Other areas often identified in these studies include the anterior and ventral temporal lobes (particularly the fusiform and parahippocampal gyri), angular gyrus, and posterior cingulate gyrus.…”
Section: Processing Of Words Compared To Pseudowords: Effects Of Leximentioning
confidence: 80%
“…The three regions that showed lexical (word > pseudoword) responses only in the Attend condition are among those frequently identified in imaging studies of semantic processing (e.g., Binder et al, 1999;Binder et al, 2003;Binder et al, 2005;Demonet et al, 1992;Mummery et al, 1998;Price et al, 1997;Roskies et al, 2001;Scott et al, 2003;Spitsyna et al, 2006). Other areas often identified in these studies include the anterior and ventral temporal lobes (particularly the fusiform and parahippocampal gyri), angular gyrus, and posterior cingulate gyrus.…”
Section: Processing Of Words Compared To Pseudowords: Effects Of Leximentioning
confidence: 80%
“…Thus, this region may participate in the recognition of many or even most visual inputs and yet also display perceptual expertise for letter strings. Several authors have reported stronger activation in this general region (and surrounding extrastriate cortex) for reading word-like pseudowords compared to words (Binder et al, 2005a;Kronbichler et al, 2004;Mechelli et al, 2003;Price et al, 1996;Xu et al, 2001). It seems very likely that this difference is related to the longer processing time and visual attention required for reading pseudowords, as the same region showed activation correlated with RT during overt word and pseudoword naming (peak at −42, −55, −10) (Binder et al, 2005a) and during a visual lexical decision task (peak at −42, −52, −17) (Binder et al, 2005b) and was activated by covert shifts of visual attention in an experiment using meaningless geometric shapes to cue the spatial location of targets (peak at −45, −69, −6) (Gitelman et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Then, small volume correction (SVC) was applied (using P 0.05, corrected) on published coordinates for a priori brain regions considered to be involved in either phonological or lexicosemantic processing. For lexicosemantic knowledge, a 10-mm radius spherical volume was used centered on [(255, 14, 221); Majerus et al, 2002] for the anterior superior temporal sulcus, [(254, 248, 26), Davis, 2004] for the posterior middle temporal gyrus, [(261, 222, 217), Majerus et al, 2002] for the inferior temporal gyrus, [(247, 283, 25), Binder et al, 2005] for the inferior parietal lobule (angular gyrus), and [(245, 35, 24), Binder et al, 1996] for the inferior frontal gyrus [Binder, 2000;Binder et al, 1996Binder et al, , 1999Binder et al, , 2005Demonet et al, 1992Demonet et al, , 1994Howard et al, 1992;Majerus et al, 2002;Perani et al, 1996;Petersen et al, 1988;Price et al, 1996;Scott et al, 2000]. Similarly, a priori regions of interest for phonological levels of representation were based on previous studies of sublexical phonological processing of speech: SVC was centered on [(260, 24, 210) and (66, 212, 0), Scott et al, 2000] for the bilateral superior temporal sulci and [(253, 243, 6) and (56 230 4), Binder et al, 2000] for the bilateral posterior superior temporal gyri [Binder, 2000;Binder and Price, 2001;Binder et al, 2000;Burton et al, 2000Burton et al, , 2005Demonet et al, 1992Demonet et al, , 1994Hickok and Poeppel, 2000;Jacquemot et al, 2003;<...>…”
Section: Discussionmentioning
confidence: 99%